1994
DOI: 10.1007/bf00228410
|View full text |Cite
|
Sign up to set email alerts
|

Transmission in a locomotor-related group Ib pathway from hindlimb extensor muscles in the cat

Abstract: It has been previously shown that phasic stimulation of group I afferents from ankle and knee extensor muscles may entrain and/or reset the intrinsic locomotor rhythm; these afferents are thus acting on motoneurones through the spinal rhythm generators. It was also concluded that the major part of these effects originates from Golgi tendon organ Ib afferents. Transmission in this pathway to lumbar motoneurones has now been investigated during fictive locomotion in spinal cats injected with nialamide and L-DOPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
241
4
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(272 citation statements)
references
References 32 publications
25
241
4
2
Order By: Relevance
“…Presence of weak EMG responses to tilts and pushes, with the temporal pattern similar to that in control, supports the second hypothesis. To test these hypotheses, in the present study we stimulated tonically two brainstem areas, which are known to affect the postural system, the MLR and VTF [10,25,26], and examined postural performance by applying lateral tilts and lateral pushes to the posterior part of the body. It was found that MLR stimulation, during the period preceding the onset of locomotion, caused an increase of the extensor muscle tone, as well as an augmentation of the EMG responses to tilts and pushes.…”
Section: Activation Of Postural Mechanisms In Postmammillary Rabbitsmentioning
confidence: 99%
“…Presence of weak EMG responses to tilts and pushes, with the temporal pattern similar to that in control, supports the second hypothesis. To test these hypotheses, in the present study we stimulated tonically two brainstem areas, which are known to affect the postural system, the MLR and VTF [10,25,26], and examined postural performance by applying lateral tilts and lateral pushes to the posterior part of the body. It was found that MLR stimulation, during the period preceding the onset of locomotion, caused an increase of the extensor muscle tone, as well as an augmentation of the EMG responses to tilts and pushes.…”
Section: Activation Of Postural Mechanisms In Postmammillary Rabbitsmentioning
confidence: 99%
“…It is thought that l-DOPA mimics the monoaminergic transmitters, which are normally released by descending pathways during periods of locomotion and facilitate the interneurones involved in the late discharges. The latter neurones were thought to be part of the 'spinal half-centers', which Brown had introduced to explain the generation of rhythmic loco motor patterns [30,31], see above.…”
Section: Evidence For Cpg In Catmentioning
confidence: 99%
“…However, neither the precise connectivity of locomotor-related spinal interneurones nor their intrinsic properties have been defined. That is, despite the demonstration that many ventral interneurones are rhythmically active during locomotor activity in the cat (Angel et al, 2005;Baev et al, 1979;Gossard et al, 1994;Huang et al, 2000;Jankowska et al, 1967a;Matsuyama et al, 2004;Shefchyk et al, 1990) and rodent (Butt and Kiehn, 2003;Butt et al, 2005;Kiehn et al, 1996;Tresch and Kiehn, 1999;Zhong et al, 2006) little is known about the connectivity of these neurones…”
Section: Introductionmentioning
confidence: 99%